Key success factors in clinical trial operation of the smallpox vaccine LC16m8 against mpox in Colombia - Tomotsugu, Naoki; Amaya-Mahecha, Maria Jose; Hamana, Mieko; Bautista-Gonzalez, María Del Mar; Gaitán-Duarte, Hernando Guillermo; Cortés, Jorge Alberto; Mine, Sohtaro; Ainai, Akira; Castellanos, Jaime E.; Tokita, Daisuke; Sugiura, Wataru; Ujiie, Mugen; et al. (Global Health & Medicine, 2025)
In 2023, the Japan Institute for Health Security (JIHS) and the Universidad Nacional de Colombia (UNAL) conducted a successful clinical trial of the LC16m8 mpox vaccine in Colombia. The joint Japan-Colombia research team categorized the trial's challenges and success factors into several key operational aspects for analysis. Key success factors were an established database of Colombian human immunodeficiency virus (HIV) patient and pre-exposure prophylaxis (PrEP) population registries, and strong experience with large-scale clinical trials of HIV and COVID-19. In addition, a strong network of infectious disease specialists in Colombia enabled close communication between the study site directors and the research team. This allowed for rapid staffing and training, which was consistent with the study schedule. The outcome of this research identifies key success factors for the immediate implementation of large-scale clinical trials and will contribute to preparedness for future pandemics.